Integrasi Lean Manufacturing Dan FMEA Dalam Pengendalian Kualitas Produk Air Minum Dalam Kemasan : Sebuah Tinjauan Literatur - Teti Febrianti; Widya Retno Prasinta (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The bottled drinking water (AMDK) industry demands consistent high quality and operational efficiency due to its direct relationship to public health. This study proposes improvements to the 330 mL bottled bottled drinking water production process at PT Muawanah Al Masoem Cikalang by integrating Lean Manufacturing and Failure Mode and Effect Analysis (FMEA) concepts. Lean Manufacturing is used to identify and eliminate waste through Value Stream Mapping (VSM), while FMEA is applied to analyze process failure risks and determine improvement priorities based on the Risk Priority Number (RPN). The integration of these two methods is expected to reduce lead times, reduce reject rates, and sustainably increase production efficiency.